ANALISIS KUALITAS PELAYANAN PEGAWAI DALAM PEMBERIAN REKOMENDASI PENDAFTARAN PAKAN DI PROVINSI LAMPUNG (Studi pada Dinas Peternakan dan Kesehatan Hewan Provinsi Lampung) - Endi Apriyadi; Ardiansyah Ardiansyah (Universitas Bandar Lampung (UBL), 2022)
Analysis of Employee Service Quality in Providing Feed Registration Recommendation in Lampung Province (Study at Lampung Province Animal Husbandry and Animal Health Service). The problems in this study are (1) How is employee service quality in providing feed registration recommendation in Lampung Province (Study at Lampung Province Animal Husbandry and Animal Health Service); (2) What aspects support and hinder in providing feed registration recommendation in Lampung Province (Study at Lampung Province Animal Husbandry and Animal Health Service).This research design uses qualitative research with qualitative descriptive analysis method which aims to describe and qualitatively analyze the quality of employee service in providing feed registration recommendation in Lampung Province (Study at Lampung Province Animal Husbandry and Animal Health Service).The research seen from the dimensions of Reliability and Assurance are still not optimal. Lack of human resources/sampling operators with competition and expertise required and no guarantee of punctuality become an obstacle in service. Tangible, Responsiveness, and Empathy dimensions in employee service quality already well. Facilities and infrastructure are adequate to provide optimal service and sampling operators are able to provide services accurately and carefully and work according to the existing Standard Operating Procedures (SOP) and are able to build good communication with consumers. In general, the service quality of the employees of Lampung Province Animal Husbandry and Animal Health Service is good but not optimal so the quality of service still can be improved.The aspects that support Employee Service Quality include : (1) Strategic location; (2) Facilities and infrastructures; (3) Free of charge; and (4) Human resources/sampling operators. The aspects that hinder Employee Service Quality are : (1) Lack of human resources/sampling operators; (2) Component of time in SOP; and (3) Reward and Punishment.